Estudio económico para determinar la viabilidad de implementación una ruta alimentadora metrovía entre la parroquia La Aurora del cantón Daule y el cantón Guayaquil - Briones Yunapanta, Steven Luciano (2025)
This study aimed to analyze the financial feasibility of implementing a feeder route for the Metro-vía system connecting the La Aurora parish in Daule with the urban center of Guayaquil, considering that the area's residential and demographic expansion has triggered a growing demand for efficient, direct, and inclusive public transport services, for which a mixed-method research approach was applied using a non-experimental and descriptive design, including structured surveys administered to 68 residents through simple random sampling at a 90% confidence level, semi structured interviews with mobility and urban transport experts, and documentary analysis of official and academic sources, which enabled triangulation of findings supported by validated theoretical and technical references, revealing that over 80% of respondents consider current transport insufficient and 91% support the implementation of a feeder route, provided it is direct, efficient, and fairly priced, while technical experts confirmed the project's operational feasibility and estimated an initial financial requirement between USD 1.5 and 2 million, a conclusion supported by the technical and economic evaluation based on coverage, accessibility, and social return indicators, determining that such a feeder route is not only viable but strategic to ensure equitable mobility, reduce travel times, promote territorial integration, and stimulate local economic activity, therefore its gradual implementation is recommended, with interinstitutional coordination, financial control, and permanent community engagement mechanisms.